Fracture toughness of 3Y-TZP ceramic measured by the Chevron-Notch Beam method: A round-robin study. Issue 7 (July 2022) - Begand, Sabine; Spintzyk, Sebastian; Geis-Gerstorfer, Jürgen; Bourauel, Christoph; Keilig, Ludger; Lohbauer, Ulrich; Worpenberg, Christin; Greuling, Andreas; Adjiski, Ranko; Jandt, Klaus D.; Lümkemann, Nina; Stawarczyk, Bogna; et al.
Abstract: Objective: This interlaboratory round robin test investigated the robustness of the Chevron-Notch Beam (CNB) test method and the effect of the processing and testing variations on the fracture toughness of a dental 3Y-TZP ceramic. Methods: The round robin test was performed precisely following the procedures recommended in ISO 24370:2005 and applied on a commercial 3Y-TZP ceramic (product information). A total of 335 test specimens with dimensions 3×4 x 45 mm³ was equally distributed among 10 participating laboratories of varying experience in fracture toughness testing. A standard operating procedure was defined with either narrow processing tolerances or alternative (wider) processing tolerances (as proposed in ISO 24370). Fracture toughness data (series 2) was analyzed using one way ANOVA followed by post hoc Tukey HSD test and 95% Confidence Intervals (CI) were computed (p < 0.05). A further, preceding round-robin (series 1) test was conducted with - more possible variations of test conditions regarding CNB notch processing and storage conditions. Those results are summarized in the supplement and discussed with the actual ISO 24370 test. Results: Fracture toughness of the 3Y-TZP ceramic material, summarized over all laboratories was measured to KIc = 4.48 ± 0.11 MPam 0.5 for the standard processing tolerance and KIc = 4.55 ± 0.31 MPam 0.5 for the alternative tolerance. The results revealed a significant influence of cutting offset and notch geometry on KIc when using CNB method. The test medium also has a significant influence on KIc in terms of reduced fracture toughness under the influence of water. With defined testing conditions the number of valid tests and reduced standard deviation increased. In case of strictly following such standard operation procedures, KIc can be determined with high reliability. There is no difference between the involved laboratories, but significant influence of cutting offset on KIC was observed. Significance: The CNB method is suitable method for determination of KIc on fine-grained ceramics such as 3Y-TZP ceramic. By using tighter tolerances for processing and testing, i.e. closely following the ISO 24370 procedure, a highly-precise evaluation of fracture toughness with low data variation is achievable. The information of the storage medium should always be reported along with the data. CNB fracture toughness testing is an alternative method compared to Single-edge V-notch beam (SEVNB), especially for fine-grained ceramics.